A review study on seed germination of papaya (Carica papaya) without presence of sarcotesta / Wan Nor Inani Wan Mohd Izani - Wan Mohd Izani, Wan Nor Inani (Faculty of Plantation and Agrotechnology, 2019)
Papaya (Carica papaya) from family Caricaceae is one of the important economical fruit crops in Malaysia. A review study on its seeds was carried out to analysis the seed germination behaviour. Typically, the fresh seeds of this fruit species obtained from the ripe fruits are readily germinable. The objective of this review study was to identify the factors that affect the rate of papaya seed germination. The treatments that influence the rate of seed germination were also studied. Due to the physiological dormancy of the seeds, the rate of papaya seed germination is slow, unequal and incomplete after desiccation. The presence of sarcotetsa as a layer that covers the seed contains inhibitor, which is phenolic compound, that causes the germination of seeds slow and non-uniform. The sarcotesta acts as a barrier to the seed germination and healthy seedling development. It is recommended that the seeds should be washed to remove the sarcostesta and dried. The removal of the sarcotesta results in increasing seed germination. On the other hand, the application of gibberellic acid (GA3) significantly promotes the germination and decreases the number of days to germination. This hormone is considered as an important germination promoter for increased seed germination, speed and uniformity, thus improving the performance of the papaya seeds.